ASSESSMENT MODEL OF HIGH SCHOOL STUDENTS’ PERFORMANCE: EXPERIENCE OF UKRAINE - Olga Bilyakovska (Borys Grinchenko Kyiv University, 2021)
The article considers modern approaches to assessment at schools based on the analysis of various assessment scales (range from three to one hundred points).